2011
DOI: 10.1159/000323075
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Masquerading as Chronic Obstructive Pulmonary Disease: A Study of Smokers Fulfilling the GOLD Definition of Chronic Obstructive Pulmonary Disease

Abstract: Background: Irreversible airways obstruction in smokers is usually attributed to chronic obstructive pulmonary disease (COPD). We speculate that some of these are cases of asthma indistinguishable from COPD. Objectives: To determine the prevalence of asthma in a ‘COPD’ population and how to differentiate the two conditions. Methods: This was a prospective observational study of smokers fulfilling the Global Initiative for Chronic Obstructive Lung Disease definition of COPD [mean post-salbutamol forced expirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 65 publications
0
48
0
Order By: Relevance
“…However, patients with asthma or COPD can share common characteristics, e.g. incompletely reversible airflow obstruction has been observed in a proportion of asthmatics and AHR can occur in patients with COPD [7,8]. The co-existence of these conditions is termed the asthma-COPD overlap syndrome, which is defined when an increased airflow variability occurs together with fixed airflow obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…However, patients with asthma or COPD can share common characteristics, e.g. incompletely reversible airflow obstruction has been observed in a proportion of asthmatics and AHR can occur in patients with COPD [7,8]. The co-existence of these conditions is termed the asthma-COPD overlap syndrome, which is defined when an increased airflow variability occurs together with fixed airflow obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Nonsmokers had greater rates of atopy, and elevated exhaled nitric oxide and eosinophil counts, all consistent with asthma. Similarly, AL-KASSIMI et al [19] studied 80 patients in Saudi Arabia aged 40-70 years with >10 pack-years smoking history who fulfilled the spirometric criteria for COPD, with post-bronchodilator FEV1/FVC <0.7 and FEV1 <80% predicted. The initial diagnosis was COPD in 46 (57.5%) patients and asthma in 34 (42.5%).…”
mentioning
confidence: 99%
“…Quite often the diagnosis can change during life and more authors report about cases of unclassified airflow limitation [16]. Moreover, it has been suggested that ACOS may include not one but several heterogeneous phenotypes with different underlying mechanisms and since these patients were previously excluded from clinical trials we have limited data of this condition [17,18].…”
Section: Reviewmentioning
confidence: 99%